Optimation of Hematopoietic Stem Cells’ Culture Medium: A Review - prasetyadi prasetyadi (Stem Cell Research and Development Center, Universitas Airlangga, 2020)
Hematopoietic stem cells (HSCs) usage has numerous potential benefits for basic and clinical research. Growing interest in this field is caused by possible HSCs application to cure various hematologic diseases, malignancies, immunodeficiency diseases, and inborn errors of metabolism. Although the demand of HSCs is increasing, ex vivo culture of HSCs has various medium compositions. This article focuses on HSCs’ culture medium optimation in different medium supplements, which might overcome non-optimal HSCs culture results. Literature searching was conducted in PubMed and google scholar database. Paper selection processes were done by author separately and studies which met the eligible criteria were included in this review. A total of 53 relevant articles were identified and 11 articles that met the eligible criteria were included in this review. There are two main types of supplement, cytokines and non-cytokines. In cytokines addition, 7 studies generally show that the supplement support HSCs expansion. The addition of non-cytokines supplements has more diverse result in studies. Positive results with various effectivity in CD34+ expansion were shown in 3 studies, while one study shows a negative result. Medium supplementation must be explored more to find best substances which can optimize HSCs culture. Further research using non-cytokines substance shall be conducted regarding its various effect and might give us a big opportunity to find an optimal condition for HSCs culture.